ESTRATÉGIAS PSICOSSOCIAIS DE RESISTÊNCIA DAS LIDERANÇAS INDÍGENAS AVÁ-GUARANI DA REGIÃO OESTE DO PARANÁ: UMA PERSPECTIVA NÃO-GERENCIALISTA NA ÁREA DE ADMINISTRAÇÃO - Menon, Rozeli Aparecida (2019)
The indigenous people in Brazil went through long periods of difficulties, mainly because of the arrival of Europeans, and after that because of the exploration of their land, characterized by violence, divestment and social exclusion. For this reason, the present study researches about the historical context of Avá-guarani peoples, which had their own rights violated and today aim for recognition and the respect for the way of being and living. The indigenous leadership, due to their communities' needs, look for solutions to solve the social problems in which they are affected. Their actions guarantee a space to allocate families to live life with dignity. In response to this reality, the study aims to comprehend the main psychosocial strategies of resistance, used by indigenous leadership, facing the violence against Aváguarani ethnicity in the west region of Paraná state. Avá-guarani people from this region are considered as a social organization, due to their way of collective life and not formal. Thus, to the Avá-guarani, the criteria to lead a group aim at preserving their social practices. Therefore, they resist to the demands of society that is not indigenous. In this context, the theory used in this study was the Latin-American communitarian social psychology, more accurately the one about psychosocial strategies of resistance, which has, as a purpose, the practice of these communities, since it embraces peoples social reality, the daily life problems, culture and social identity, as a way of lessening the suffering and improve their living conditions. This theory encompass the awareness process in relation to the historical memory and political reaction. That way, it is relevant to understand the challenges that the indigenous leadership face today in their land, even for the lack of attention to their social problems. The qualitative method was used in this study, considering the indigenous leadership as an analytical category. The gather of information covered the mais leaders of Tekoha, located in the west region of Parana. It was carried out with 13 indigenous leaderships, being themselves the main participants of fights to assure their rights. They served as collection instrument to the participant observation, semi structured interviews and description field. To obtain results, the analyses of thematic oral history was used, aiming to relate the every day and historical experiences of the Avá-guarani people, explaining their social practices in community. These results were positive, entailing the knowledge of the reality, where it is noticed that the indigenous leadership are politically articulated. They fight and resist, likewise facing problems in their communities, lack of resources and basic life conditions. Seeking to solve problems using the dialog. The language, the main way of communication between the communities, goes through generations and it still keeps its strength. There is a constant concern of the indigenous leaderships to preserve it. They try to unite as community goal of protecting the culture and customs and, mainly, to retrieve their land. Land is considered part of their being, because the social organization is tied to it to the subsistence cultivation and to the practice of religion through chanting, dancing and praying. The ideal to these people is to continue with their way of being and living.